Simulação de configurações de movimentação de um sistema AGV para transporte em posto de pintura especial - Assis, Rafael de (2024)
This dissertation presents a proposed solution for the movement of products in process, simulating the use of AGV vehicles in the special painting process at a manufacturer of drives for the industry. The research objective is to analyze potential productivity gains that AGV can bring to this process, primarily by reducing the lead time, which directly impacts product lead time. Based on the experimentation method that utilizes simulation, this study presents 3 models: the current situation, the implementation of deck lift AGV, and the implementation of tugger AGV. Comparing the models based on performance indicators highlights productivity gains, concluding that the best model is the deck lift AGV, which yields results such as a 99.17% decrease in waiting time and improvements in lead time gain indicators ranging from 33.78% to 92.16%, depending on the type of painting, as well as better space utilization, 84.76% lower compared to the current situation. The characteristic of the deck lift AGV model to transport the product when it is placed in the output buffer of the special painting station has been shown to improve productivity gains, presenting favorable conditions for sector organization and directly influencing management quality and customer satisfaction.